Phosphorus and nitrogen fertilization of soybean in the Nigerian savanna - Kamara, A.Y.; Ekeleme, F.; Omoigui, L.O.; Ajeigbe, Hakeem A. (Cambridge University Press, 2012)
Soybean (Glycine max) is a major cash crop in the savannas of Nigeria although productivity is typically constrained by poor soil fertility. The objective of this research was to determine the interactive effect of N and P on soybean productivity in the northern Guinea and Sudan savannas of northeast Nigeria. Experiments were conducted using locally adapted early and late maturing cultivars. Two rates of N and three rates of P fertilizer were also compared at both sites over two years. At both sites, pods plant−1 and seed yield were higher in 2006 than in 2007, possibly due to better rainfall distribution in 2006. Nitrogen fertilizer had no significant effect on seed yield or pods plant−1. Application of P fertilizer increased pods plant−1 by 40–66%. Averaged across site and year, seed yield with no P was 1057.2 kg ha−1 while yield with 20 and 40 kg ha−1 P were 1941.0 kg ha−1 and 2371.5 kg ha−1, respectively. No significant interaction effect between N and P fertilizer on seed yield and pods plant−1 was observed. The late maturing cultivar yielded less than the earlier maturity group cultivar in 2007 likely due to moisture stress. For optimum seed yield 40 kg of P fertilizer ha−1 is recommended for soybean production in both locations. Our results suggest that N fertilizer is not critical for soybean production in this area.